A quality evaluation methodology of health web-pages for non-professionals. - Curro, Vincenzo (Medical informatics and the intrenet in medicine :an international journal of information processing in health care.)
The proposal of an evaluation methodology for determining the quality of healthcare web sites for the dissemination of medical information to non-profesionals. Three (macro) factors are considered for the quality evaluation: medical contents, accountability of the authors, and usability of the web site. Starting from two results in the literature the problem of whether or not to introduce a weighting function has been investigated. This methodology has been validated on a specialized information content, i.e., sore throats, due to the large interest such a topic enjoys with target users. The World Wide Web was accessed using a meta-search system merging several search engines. A statistical analysis was made to compare the proposed methodology with the obtained ranks of the sample web pages. The statistical analysis confirms that the variables examined (per item and sub factor) show substantially similar ranks and are capable of contributing to the evaluation of the main quality macro factors. A comparison between the aggregation functions in the proposed methodology (non-weighted averages) and the weighting functions, derived from the literature, allowed us to verify the suitability of the method. The proposed methodology suggests a simple approach which can quickly award an overall quality score for medical web sites oriented to non-professionals.